Effects of social media use on family relationship quality: a systematic review / Nan Wu and Siti Ezaleila Mustafa - Wu, Nan; Mustafa, Siti Ezaleila (Faculty of Communication and Media Studies (FCMS), 2023)
The emergence and popularity of social media may lead to changes in family communication and have many impacts on family relationships. The purpose of this paper is to systematically review the literature on the effects of social media use on family relationship quality. This paper searched five databases for English-written papers published in academic journals between 2012 and 2022. A total of 44 papers were included. The review results showed that social media had significant benefits for family relationships but also exacerbated some of the challenges in family life. Social media had different impacts on different types of family relationships, namely marital relationships, intergenerational relationships, and the family as a whole. Specifically, the use of social media has more negative effects on marital relationships but more positive effects on intergenerational relationships. In addition, different types of social media have different effects on family relationship quality. Compared to network-oriented public social media, integrated and closed social media is more conducive to enhancing family relationship quality.